Screening tools for identifying a high probability of obstructive sleep apnea - Svaza, Juris; Grava, Jekaterina; Smolko, Jana (Acta medica Lituanica, 2012)
Background. Obstructive sleep apnea (OSA) is a common medical problem that affects up to 5% of the population. The majority of OSA patients are undiagnosed and have a potential for perioperative complications. Our study was conducted to validate the most widely used screening tools for identifying high risk OSA patients and to find the most predictable physical signs and symptoms of OSA. Materials and methods. At the Sleep Laboratory of Riga Stradins University, 100 patients with suspected OSA were asked to fill in patient questionnaires prior to the sleep study. The patients’ anthropometric data, physical signs and medical history were collected. To confirm the diagnosis of OSA, all patients underwent a full night sleep study. To find the possible correlation, the data collected from the questionnaires were compared with the data from sleep studies. Results. Patients (n = 100) at a mean age of 47 yrs. (23–73), 22 women, 78 men. No OSA was found in 17%, mild OSA in 23%, moderate OSA in 21%, severe OSA in 39% of the patients. A strong correlation between the body mass index (BMI; p
Keywords: obstructive sleep apnea; perioperative risk